Educational Media Design for Organic Waste Management through Black Soldier Fly Maggot Cultivation - Ardiansyah, Hafid; Wicaksono, Arif Ranu (Journal of Visual Communication Design, 2026)
The increasing volume of organic waste in residential areas remains a significant environmental issue, particularly due to limited public understanding of proper waste management methods. The lack of effective visual educational media has become a key challenge in supporting community understanding of organic waste management using Black Soldier Fly (BSF) maggots in Mojosongo, Surakarta. This study aims to design an educational e-book as a visual communication medium to address this issue. The research applies the Design Thinking method, consisting of empathize, define, ideate, prototype, and test stages, to develop a user-centered design. The resulting e-book integrates structured content with visual elements to enhance clarity and comprehension. Evaluation through beta testing involving 25 respondents shows a feasibility score of 87.6%, indicating high suitability. The findings indicate that the e-book is feasible and has strong potential to support community understanding.